Analisis Sentimen Pengguna E-Wallet GOPAY, OVO, dan DANA Menggunakan Algoritma Random Forest - Mardiana Purwaningsih; Andika; Rehan RamadhanSyah; Alrafiful Rahman (POLITEKNIK NEGERI JAKARTA, 2026)
Abstract - The development of digital payment systems in Indonesia has accelerated significantly with the introduction of the Quick Response Code Indonesian Standard (QRIS), which enables cashless transactions across various digital wallet platforms. GoPay, OVO, and DANA are three popular digital wallet applications that support payments using QRIS. This study aims to analyze and compare the use of the QRIS feature in these three applications based on user reviews on the Google Play Store. The method used is sentiment analysis employing the Random Forest algorithm, utilizing a total of 25,000 reviews proportionally collected from each application. The analysis process includes text cleaning, tokenization, stopword removal, stemming, and sentiment classification into positive, negative, and neutral categories. The results of the study show that GoPay has the highest percentage of positive reviews related to QRIS at 70%, followed by DANA at 65%, and OVO at 50%. Furthermore, GoPay also recorded the highest volume of QRIS-related reviews compared to the other two applications. Based on these findings, it can be concluded that GoPay is the most widely used and appreciated application in the context of QRIS-based transactions. This study may serve as a reference for application developers in enhancing digital payment services in Indonesia.